2022
DOI: 10.1371/journal.pone.0276761
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and physical activity: A prospective cohort study

Abstract: Diabetes is on the rise as the worldwide population ages. While physical activity can help protect against diabetes, ageing is commonly associated with reduced physical activity. This study aimed to examine if physical activity differs by diabetes status in mid-aged adults, how this association changes over time, and whether physical activity-related sociodemographic factors and health indicators differ in those with and without diabetes. Data came from four waves of the How Areas in Brisbane Influence HealTh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In another population-based study, Attanayake et al [21], it was found that people with diabetes undertook less physical activity than people without diabetes and this was consistent over time. The strongest predictor for people with diabetes, whether or not they engaged in sport, was gender and BMI.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In another population-based study, Attanayake et al [21], it was found that people with diabetes undertook less physical activity than people without diabetes and this was consistent over time. The strongest predictor for people with diabetes, whether or not they engaged in sport, was gender and BMI.…”
Section: Introductionmentioning
confidence: 89%
“…People with diabetes were less active and had a higher BMI than people without diabetes. Other issues that may contribute to low activity among people with diabetes include physical or cognitive disability, depressive symptoms, and poor sleep [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Attanayake et al [10], the research revealed that people with diabetes were engaging in less physical activity compared to those without diabetes, and this was consistent over time. The strongest predictors of physical activity for people with diabetes, whether or not they engaged in sport, were gender and BMI.…”
Section: Introductionmentioning
confidence: 96%
“…People with diabetes were less active and had a higher BMI than people without diabetes. Other issues that may contribute to low activity among people with diabetes include physical or cognitive disability, depressive symptoms, and poor sleep [10].…”
Section: Introductionmentioning
confidence: 99%